(untitled) (Innovate Conferences, 2025)
Altruism, defined as selfless concern for the well-being of others, is a fundamental aspect of human morality and social cohesion. This paper explores the philosophical dimensions of fostering altruism in youth, examining various ethical theories and their implications for educational practices. By analyzing the works of prominent philosophers and contemporary thinkers, this study aims to provide a framework for nurturing altruistic values in young individuals. This paper provides a philosophical exploration into fostering altruism in youth, emphasizing that nurturing these values is crucial for personal development and societal well-being.